Model Pembelajaran Think Talk Write dan Motivasi Belajar terhadap Hasil Belajar Bahasa Indonesia - Mahmud Haris Al Amin; Engelberthus Kukuh W (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2020)
This study aims to determine the effect of Think Talk Write learning models on motivation and learning outcomes in Indonesian. The research design used was nonequivalent post-test only control group design. The population in this study were all grade IV SD 3 Sidoluhur, Lawang Malang Regency in the 2018/2019 school year. Samples were taken by random sampling technique. The data collected was analyzed with the MANOVA test. The results showed that: 1) there were significant differences in learning motivation between groups of students who were taught with Think Talk Write learning models and groups of students who were taught with conventional learning models 2) there were significant differences in Indonesian learning outcomes between groups of students who were taught with models Think to Talk Write learning and student groups that are taught with conventional learning models, 3) there are significant differences in learning motivation and Indonesian language learning outcomes between groups of students who are taught with Think Talk Write learning models and groups of students who are taught with conventional learning models.